ANTI-MINE ACTION AND LIBERAL PEACE IN CASAMANCE, SENEGAL - Salichs,Tomas Serna (2021)
Abstract This paper proposes a reading of the “neither peace nor war” setting in Casamance, Senegal, one of the more persistent conflicts in West Africa. It examines peacebuilding and development policies through a comprehensive review lens of existing literature and field knowledge to analyze the failure of the anti-mine program. The paper argues that the anti-mine development policy and peacebuilding outline applied in Casamance relates to the discourse and framework of liberal peace. It reveals that the mindset of the liberal peace agenda is not consistent with the dialogue required to achieve a sustainable peace and implement an effective demining program.